The global development of cryptocurrencies - Miciuła, Ireneusz; Kazojć, Katarzyna (Globalny rozwój kryptowalut, 2019)
The global crypto marketplace has an impact on the functioning of financial markets and has huge implications for entire economies. The article discusses the functioning of the global cryptocurrency market, and based on the analysis of the history of the most popular cryptocurrency, bitcoin, an attempt was made to determine possible development prospects. The aim of the article is to assess the development of the current crypto marketplace in the world and to present possible development prospects. The foresight method was used to implement the research objective, in particular trend analysis (quantitative data) and discrete event system (qualitative and expert data). This allows us to learn about the regularity of the cryptocurrencies in the sphere of investment management from the investors' point of view and the creation of an appropriate legal framework by the supervisory authorities and ensuring the social security of the financial system
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 2, s. 183-196
Keywords: cryptocurrencies; financial innovation; global financial market; legal regulations of the market; technological and financial changes; FinTech; kryptowaluty; innowacje finansowe; globalny rynek finansowy; regulacje prawne rynku; zmiany technologiczno-finansowe